Analisis Pemasaran Tandan Buah Segar Kelapa Sawit Di Kabupaten Kutai Kartanegara (Studi Kasus Pada Petani Swadaya Kecamatan Kota Bangun) - Agung Enggal Nugroho (Jurnal Magrobis, 2017)
The purpose of this study was to determine: (1) marketing channels palm oil, (2) share received by oil palm growers, (3) assess the factors that cause fluctuations in the price of oil palm FFB Kota Bangun District.The results of this study indicate that in Kota Bangun District there are two types of FFB marketing channels, which is a two-level and three level channel. At two level channel, share received by farmers was 74.71%, while the three-level channels, the share received by farmers is 74%.The results also show that there are two factors that affect the price fluctuations FFB farm level, the purchase price of existing palm oil mill and marketing costs (transport, labor costs of transportation and expected return). Prices at the mill itself following the instructions Estate and Forestry Service of East Kalimantan that updated every month.Keywords: Marketing, Palm_Oil